Study on spatial turning maneuver of underwater towed system for submersibles - Wang Zhibo; Kong Peiyun (Scientific Reports)
Abstract The spatial turning motion of a submersible is a crucial maneuvering mode that significantly affects the dynamic performance and stability of an underwater towed system. To quantitatively capture the key influencing factors, a set of dimensionless parameters is introduced. A dynamic model is developed based on the lumped mass method, incorporating the six-degree-of-freedom maneuvering motion of the submersible and the nonlinear dynamics of the flexible towed cable. Parametric studies are conducted by varying five dimensionless ratios: the turning radius to cable length R/L, total cable mass to towed body mass ω, cable unit mass to unit drag w/r, horizontal to vertical speed ratio V ζ /V t , and cable buoyancy to gravity B c /G c ​. Results show that when R/L increases from 0.05 to 1.0, the steady-state tension drops by approximately 20. Increasing V ζ /V t from 20 to 80 shortens the transient stage by 87.5%. The system achieves minimum tension when R/L = 1.0, indicating optimal vertical force balance. These findings reveal clear dynamic trends and provide guidance for parameter optimization in submersible-towed systems under complex 3D motion.